Claws for concern - James, Miranda (James, Miranda. Cat in the stacks mystery., 2018)
"Charlie Harris and his Maine Coon cat, Diesel, are embroiled in a new mystery when a cold case suddenly heats up in the latest installment of the New York Times bestselling series. Charlie Harris has been enjoying some peace and quiet with his new grandson when a mysterious man with a connection to an unsolved murder starts visiting the library.."--